Veni, vidi, vici: the success of wtf meiotic drivers in fission yeast - López Hernández, José Fabricio (Yeast, 2018)
Meiotic drivers are selfish DNA loci that can bias their own transmission into gametes. Owing to their transmission advantages, meiotic drivers can spread in populations even if the drivers or linked variants decrease organismal fitness. Meiotic drive was first formally described in the 1950s and is thought to be a powerful force shaping eukaryotic genomes. Classic genetic analyses have detected the action of meiotic drivers in plants, filamentous fungi, insects and vertebrates. Several of these drive systems have limited experimental tractability and relatively little is known about the molecular mechanisms of meiotic drive. Recently, however, meiotic drivers were discovered in a yeast species. The Schizosaccharomyces pombe wtf gene family contains several active meiotic drive genes. This review summarizes what is known about the wtf family and highlights its potential as a highly tractable experimental model for molecular and evolutionary characterization of meiotic drive.